Enhancing Entrepreneurial Skills through Co-opetitive learning experience: A Case Study in a Spanish University - Erdmann, Anett; García-Monleón, Fernando; Nuñez-Canal, Margarita (Journal of Management and Business Education, 2022)
Global competition and digital market forces imply opportunities and threats in an increasingly fast and competitive job market. In this context, motivated learning through collaboration or cooperation have been extensively studied to develop necessary skills to be competitive. However, in undergraduate teaching little attention has been given to learning through competition and co-opetition, which is more common in entrepreneurial education. This paper proposes and tests a new classroom methodology where undergraduate students in the course Microeconomics interact in teams playing out features of the four C’s of game-based learning in an entrepreneurial environment: cooperation, collaboration, competition and co-opetition. The pedagogical pilot-project, dubbed as “Micro-Challenge”, is a peer-based student challenge which has been implemented in face-to-face classes as well as in a hybrid classroom. A posterior analysis of survey data and academic results, using regression analysis, reveals that the development of collaborative skills and team-based skills depend on personal characteristics and expertise while there is no significant effect of academic performance. Moreover, women are more likely to improve team-working or collaborative skills through the proposed challenge than men and engagement in terms of induced learning effect is found to be higher for students who are already endowed with a high level of competitive or collaborative attitude.